To describe Modernity: Gracián, Ortega, Lotman - Talvet, Jueri (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
The present article is an attempt to characterize the position assumed before the complex and ever polemical phenomenon of Modernity by three great representatives of dialogical-relativist thought: the baroque writer Baltasar Gracián (1601-1658), the theorist of the 20th-century avantgardes José Ortega y Gasset (1883-1955) and the leader of the Tartu School of Semiotics, Yuri Lotman (1922-1993).Both in the 17th and the 20th centuries Modernity is an aspiration to accept the relativist dialectics of the sign or the permanent dynamics of significations. Modern openness means a constant desire to rebel against established systems and to "leap" into nature, which embodies a "virgin field" for new intelIectual and cultural realizations.Even so, the description of Modernity still hides ambiguities. It will thus remain an enigma if the plurilingual and polylogical "frontiers" conceived by Lotman as premises for cultural "explosions" and subsequent "Ieaps" into different social and cultural systems are sufficient to confront the ever more agressive closure imposed by the powerful commercial mechanisms of Western civilization.
Keywords: Baltasar Gracián; José Ortega y Gasset; Iuri Lotman